PERLAWANAN PIHAK KETIGA (DERDEN VERZET) TERHADAP EKSEKUSI BARANG BUKTI ATAS PUTUSAN PENGADILAN YANG TELAH BERKEKUATAN HUKUM TETAP( INKRACHT VAN GEWIJSDE) TERKAIT TINDAK PIDANA - Fatria Gunawan (JURNAL AKTA YUDISIA, 2020)
ABSTRACT A judge's decision concerning evidence in a criminal case is not closed, possibly causing problems in the future. Including the emergence of resistance by third parties who feel that their rights and interests have been harmed by the evidence.The research method used is a normative juridical research method with a conceptual approach, a legal approach and case approach.Based on the results of the study can be concluded first; Ratio Desidendy the decision of the Binjai District Court Number: 22 / Pdt.Plw / 2012 / PN.BJ dated 21 February 2013 that resistance was the guarantor of Darman's debt to the CV Showroom. Jaya Mobilindo because of the principal agreement to buy and  sell 1 unit of car carried out by Darman with CV Showroom. Jaya Mobilindo, where resistance does not know the relationship between Darman and the Survived Als. Adi related to the a quo car unit. Therefore according to the provisions of article 24 of Law No. 42 of 1999 concerning the Fiduciary Guarantee above, then The opponent should not be burdened with the obligation  to bear the risk of loss of objects that are used as fiduciary guarantees for unlawful acts committed by Suriadi Als. Adi, Defendant in Case No. 265 / Pid.B / 2012 / PN.BJ. Therefore, opponents are third parties with good intentions that must be protected by their rights and interests.Second: The third party's legal efforts to defend civil rights against the execution of evidence related to criminal offenses are by carrying out resistance efforts (derdenverzet. As an extraordinary legal measure used by third parties to refute or fight the execution of seizures carried out by the court. this law is carried out by third parties with the intention that their rights and interests are harmed as a result of the execution of seizure to get legal protection.Criminal legal measures can also be taken by third parties when their interests and rights are harmed as a result of a court decision in a criminal case. Third party property is used as evidence in a criminal case, because it is used by the defendant in committing a crime, so that one of the dictums of the court decision in the criminal case is confiscating evidence for a country that is actually owned by a third party that is not involved am criminal case. Keywords, Derden Verzet, Decision, Execution, Evidence, Criminal Act